Increasing efficiency in the production process of drinking water using lean technical: Case study of drinking water Thanthip production - Impho, Wairut (Creative Science, 2017)
This research aims to study the production of drinking water and identify methods to improve its efficiency by reducing waste in the tharnthip drinking water production in order to increase its efficiency. The job analysis according lean concept the application of the 5W1H principle and ECRS were used to provide an overview of the water production process of 20 liters tank of drinking water. It can be found that there were 17 working procedures before work improvement and there were 15 working procedures after work improvement. Thus 2 working procedures were reduced representing 11.76%. The distance of movement was reduced from 51 meters to 20 meters or 31 meters reduced were achieved representing 60.79%. Time spent in production before work improvement was 263.24 seconds and after work improvement it was 169.16 seconds. Thus production time was reduced 94.08 seconds representing 35.71%.